Peranan Kepemimpinan Kepala Madrasah Dalam Meningkatkan Kompetensi Kepribadian Dan Etos Guru Pendidikan Agama Islam Madrasah Ibtidaiyyah Negeri 1 Pinangsori Kabupaten Tapanuli Tengah - Ilham Syarif (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2020)
The leadership of the Pinangsori 1 Ibtidaiyyah State Madrasah Principal must be able to strive to improve teacher competence, so that teachers, especially Islamic religious education teachers, have personal competence and perseverance in working based on their profession.The type of research is phenomenological qualitative research. The place and time of this study have characteristics including the actual setting. The researcher is a key instrument, and the data is descriptive.Based on the data and analysis of this study, it was found that the personal competence of Islamic religious education teachers in the Pinangsori State Ibtidaiyyah 1 Madrasah basically reflected personality competencies which should be owned by an Islamic religious education teacher, such as believers and pious, noble, patient and sincere in carrying out their duties , wise and wise, democratic, and so on. The ethos of Islamic religious education teachers is carried out full of enthusiasm, responsibility, patience, enthusiasm, and others. The role of the headmaster in increasing the competence of the personality of Islamic religious education teachers consists of the formation of habituation, formation of understanding, and the formation of a noble spirituality. The role of the headmaster in improving the ethos of Islamic religious education teachers in the form of conducting discussions, providing awareness to teachers for a lot of reading and learning, providing opportunities for teachers to attend various trainings, providing teacher main tasks, asking teachers to prepare syllabus, and also conducting class visits. Supporting factors are the awareness of each teacher of his duties and responsibilities and the establishment of a family atmosphere. While inhibiting factors are related to the age of the teacher, fear of hurting the teacher's heart, and the limitations of facilities and infrastructure.